THE STRATEGY OF REACHING THE INTERNATIONAL MARKET SHARE FOR PT. HILDAN FATHONI INDONESIA - Bhisma Maha Santika; Chrissant Dea Arini; Wenseslaus Salivian K; Simon Peter Q Ortega; Charles W Kleinman; Fatemah H Y Y M Almudhahkah; Dhairi M M N R Al Meseb (AIBPM Publisher, 2018)
PT. Hildan Fathoni Indonesia is a company that has two product lines, such as product safety, product and crafts. As the company does not yet have the experience in terms of export products. Therefore, a much-needed strategy to sell the company's products with the scale Internatioal. PT. Hildan Fathoni makes the United States as a target market. its marketing strategy using articles and YouTube with the title that is effetive and in accordance with the research that's been done.